A Critical Review of the Book Iranian Identity: From Antiquity to the End of Pahlavi - Reza Bigdelou (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Identity, or the examination of who and what man is, has developed as a type of historical awareness and serves a variety of individual and societal functions. Due to the complexity of the identification process and the vastness of layers and aspects of identity, the growth of globalization, the establishment of modern and postmodern educational institutions and frameworks to describe its principles, elements, and functions, and the implications of recent political, social, and economic events, the subject of identity has become a critical and fundamental concern. In Iran also, identity has emerged as a critical social, political, and scientific issue. The purpose of this article is to perform a critical examination of the book Iranian Identity: From Antiquity to the End of Pahlavi emphasizing both its strengths and weaknesses. The study's findings signify that the book has become a widely cited source in the Iranian scientific ـ research community as a result of its theoretical principles and research methodology; however, the book's lack of operational definitions for key concepts, emphasis on Iranian identity discussion while ignoring other identity discussions, and inconsistencies in the theoretical and methodological framework, reliance on the periods of political history, and a neglect of the challenges resulting from the confrontation between Iranian and national identities, all contribute to the book's shortcomings.